Social Capital in Covid-19 Pandemic Period in Indonesia: Literature Review of Social Capital Implementation - Kurdeniansyah Kurdeniansyah; Elli Nur Hayati (Psychosophia: Journal of Psychology, Religion, and Humanity, 2023)
The purpose of this research is to describe social capital in the society in time of the pandemic situation of Covid-19 in the case of psychology perspective. The method in this research uses a literature research method collected from scientific papers including devotion programs which explain the pandemic of Covid-19 situation. It was collected from some databases such as Google Scholar, Science Direct, Research Gate, Garuda also some scientific writing of the university. The process of examine including selective steps to analyze some background and also some regions in Indonesia. The result discovers psychological contexts such as trust, norms, reciprocity, resilience, cooperation, and social network correlated to social capital which is represented through programs, activity, and local wisdom surrounding society.